1997
DOI: 10.1021/om960789f
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Study of the Insertion of Norbornadiene into Palladium−Carbon Bonds of Complexes Containing the Rigid Bidentate Nitrogen Ligand Bis(arylimino)acenaphthene

Abstract: Kinetic study of the insertion of norbornadiene into palladium-carbon bonds of complexes containing the rigid bidentate nitrogen ligand Bis(arylimino)acenaphtene Groen, J.H.; Delis, J.G.P.; van Leeuwen, P.W.N.M.; Vrieze, K. Published in: Organometallics DOI:10.1021/om960789fLink to publication Citation for published version (APA):Groen, J. H., Delis, J. G. P., van Leeuwen, P. W. N. M., & Vrieze, K. (1997). Kinetic study of the insertion of norbornadiene into palladium-carbon bonds of complexes containing the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
53
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(58 citation statements)
references
References 64 publications
5
53
0
Order By: Relevance
“…A smaller amount of energy is required to displace the B(C 6 F 5 ) 4 À anion from the first coordination sphere but, because of the fact that the degrees of mobility of B(C 6 F 5 ) 4 À are similar in ISIPs and OSIPs, the recovery of entropy is smaller and approaches the typical value of DS°of an associative bimolecular process occurring in low polar solvents (around À50 cal mol À1 K À1 ). [36][37][38][39] Notably, almost the same recovery of entropy (DS°= À44 AE 5 cal mol À1 K À1 ) was observed for the sole olefin polymerization catalyst with the MeB(C 6 F 5 ) 3 À counterion in the second coordination sphere. [29] The insertion of 2 in 1a and 1b is around 3-5 and 50-100 times slower, respectively, in [D 8 ]toluene/[D 5 ]chlorobenzene than in [D 8 ]toluene (DDG°= 0.5-1.0 and 2.2-2.5 kcal mol À1 for 1a and 1b, respectively) and the anion has no effect on the insertion rate (Table 1, entries 9-16).…”
Section: Angewandte Chemiesupporting
confidence: 57%
“…A smaller amount of energy is required to displace the B(C 6 F 5 ) 4 À anion from the first coordination sphere but, because of the fact that the degrees of mobility of B(C 6 F 5 ) 4 À are similar in ISIPs and OSIPs, the recovery of entropy is smaller and approaches the typical value of DS°of an associative bimolecular process occurring in low polar solvents (around À50 cal mol À1 K À1 ). [36][37][38][39] Notably, almost the same recovery of entropy (DS°= À44 AE 5 cal mol À1 K À1 ) was observed for the sole olefin polymerization catalyst with the MeB(C 6 F 5 ) 3 À counterion in the second coordination sphere. [29] The insertion of 2 in 1a and 1b is around 3-5 and 50-100 times slower, respectively, in [D 8 ]toluene/[D 5 ]chlorobenzene than in [D 8 ]toluene (DDG°= 0.5-1.0 and 2.2-2.5 kcal mol À1 for 1a and 1b, respectively) and the anion has no effect on the insertion rate (Table 1, entries 9-16).…”
Section: Angewandte Chemiesupporting
confidence: 57%
“…[46] The Ar-BIAN system is a highly stable, rigid bidentate spectator ligand with interesting electronic properties. [47,48] Elsevier and co-workers suggested that Ar-BIAN ligands may act as stronger σ-donors toward the metal when compared to bpy, and also proposed that the rigid Ar-BIAN ligands are rather comparable to open chain R-DAB analogues in electronic properties, which would be the case if the diimine system in the Ar-BIAN ligands is electronically isolated from and has no conjugation with the naphthalene backbone.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the reaction chemistry of this class of diimine ligand with a variety of transition metals has become well established [1,[3][4][5][6][7][8]. Lately, the interest in early transition metal chemistry has focused on group 6 complexes that contain chelating diazadiene ligands [9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%